Effect of Heat Softening versus Ultrasonic Removal of Root-End Gutta-Percha on the Quality of Root-End Preparation for Endodontic Microsurgery. (3rd August 2021) - Ling, Zhiting; Zheng, Ziting; Zeng, Yuting; Jiang, Lifang; Wu, Yuan; Wu, Buling; Yan, Wenjuan
Abstract : This study is aimed at comparing the efficacy of heat softening and ultrasonic removal of root-end gutta-percha during retrograde preparation for root apical microsurgery. Recently extracted single-rooted premolars (n = 40 ) were prepared with standardized endodontically treated and root-end resection and then randomly divided into four groups that received root-end cavity preparation using four different instruments: a diamond-coated ultrasonic tip (AS3D; SACTEON, Paris, France), AS3D with the modified plugger of cordless heat carrier (MSE; B&L Biotech, Bala Cynwyd, PA, USA), stainless steel ultrasonic tip (Jetip-2; B&L Biotech, Bala Cynwyd, PA, USA), or Jetip-2 with MSE. The time required for root-end preparation was recorded. The root apex samples were examined by scanning electron microscopy to assess root surface microcracks and marginal integrity. The remnants of gutta-percha on the cavity walls were evaluated using a stereomicroscope. Statistical analysis was performed using Student's t -test and Wilcoxon rank-sum test (P < 0.05 ). Usage of MSE with Jetip-2 significantly reduced preparation time from 99.8 ± 6.8 s to 32.4 ± 1.0 s (P = 0.009 ), the number of microcracks from 42 to 13 (P = 0.036 ), and the remnants of gutta-percha from 80% to 20% (P = 0.041 ). Similar results were observed for AS3D with MSE. The heat softening of MSE was effective in cleaning gutta-percha, thus greatly improving the efficiency of the root-end preparation, thereby producing a root-end cavity with fewer microcracks and better marginal integrity.